LEGAL STATUS OF THE CHAMBER OF ADVOCATES (World Bulletin of Management and Law, 2022)
The article deals with some issues related to the professional activities of a lawyer and the legal status of the Chamber of Advocates. The author explores the rights and obligations of lawyers as professionals who provide citizens with qualified legal assistance.
Keywords: bar association; defender; principal